Child, Family, and Community - Laff, Rebecca; Ruiz, Wendy (Open textbook library., 2019)
Over the years researchers have found the necessity to develop theories of behavior that are specific to family settings. These theories have been developed by people with a variety of areas of emphasis, from family therapists to gerontologists to child development specialists. In this chapter we will briefly discuss six such theories: Bioecological Model, Family Systems, Functionalism, Conflict Theory, Symbolic Interactionism, and Psychological Perspectives.